Impact of Body Mass Index on Number of Lymph Nodes Retrieved in Gastric Cancer Patients - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2014)
Background/Aims: The aim of this study was to assess the influence of obesity on the number of the dissected lymph nodes in patients who underwent gastrectomy for gastric adenocarcinoma. Methodology: Thirty eight Patients with gastric adenocarcinoma who underwent curative gastrectomy at one center between April 2012 and December 2012 were eligible for the study. According to their body mass index (BMI) values before surgery patients with BMI >= 24.9 kg/m(2) were defined as obese. Patients with BMI <= 24.9 kg/m(2) were defined as normal group. The number of retrieved lymph nodes and metastatic lymph nodes were obtained from pathology reports. Results: Among 38 patients there were 17 (45%) patients had BMI <= 24.9kg/m(2) (normal group),while 21(%55) patients had BMI>24.9 kg/m(2) (obese group). The median number of retrieved lymph nodes in obese patients who underwent total gastrectomy was significantly higher compared to the normal patients underwent the same procedure. Conclusion: In this study we showed that the obesity affects the outcomes of surgery in gastric cancer. Furthermore, the total number of retrieved lymph nodes in obese patients who underwent total gastrectomy was higher than that in non-obese patients.
Keywords: Gastric cancer; Lymph node; Body Mass Index; Obesity; COMPUTED-TOMOGRAPHY; BREAST-CANCER; OBESITY; GASTRECTOMY; DISSECTION; OUTCOMES; WOMEN; FAT